Comparison of SAW, AHP, and TOPSIS Methods in a Decision Support System for Teacher Performance Evaluation - Deta, Bernadete; Bedanaen, Sesilia M. Ina (LifeSciFi, 2025)
Teachers are one of the important elements that schools must have in order to improve educational services. Teachers must always be motivated to provide the best educational services to their students, so that schools can improve the quality of schools to become great flagship schools. One effort to improve school quality is by evaluating teacher performance assessments. Conducting teacher performance assessments is an analytical process that aims to create better teaching and educational services. The teacher performance assessment process is still carried out manually and no specific methods are applied. With an assessment that is not detailed, it is feared that there will be subjective assessments and can have an impact on some parties that may be unfavorable. Therefore, to overcome the resulting decisions, a decision support system is needed by applying the SAW, AHP, and TOPSIS methods. Based on the results of the accuracy and suitability levels, the comparison of the total percentage of the SAW, AHP, and TOPSIS methods on both types of teacher performance regulations has the same suitability percentage of 99.99% and the same accuracy level of 100%, but there are differences in each resulting preference value.